Tinjauan Yuridis Persaingan Usaha Tidak Sehat Terhadap Usaha Besar dengan UMKM dalam Perspektif UU No. 20 Tahun 2008 (Studi Kasus Putusan Perkara Nomor 02/KPPU-K/2020) - Irma, Febriana; Gunadi, Ariawan (UNES Law Review, 2023)
This research discusses the judicial review Unfair Business Competition Against Large Businesses and MSMEs in the Perspective of Law no. 20 of 2008. The primary focus of the study is the violation of Article 35 paragraph (1) of Law No. 20 of 2008 concerning Micro, Small, and Medium Enterprises, which prohibits "large enterprises from owning and/or controlling MSMEs as partners in their partnership relationships." Through a case study of the decision by the Business Competition Supervisory Commission (KPPU), this research analyzes the legal implications of such violations and their impact on business competition. The research methodology involves legal analysis and the comparison of related cases. The findings reveal the importance of law enforcement in maintaining a fair and healthy business competition environment, safeguarding MSMEs, and promoting sustainable economic development. These findings provide insights for policymakers and legal practitioners in preserving fair and equitable business competition within the MSME sector.